Analisis Pengaruh Diabetes Mellitus Self Management terhadap Resiko Penyakit Komplikasi di Desa Saentis Kabupaten Deli Serdang (Studi Kasus pada Klinik Harapan Jaya) - Raysha Awlia Wijaya; Bayu Ariatama; Ermawati MH Siregar; Meifi Elfira (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Diabetes mellitus self-management refers to actions taken by an individual to independently control and manage the disease—including treatment measures and complication prevention—with the aim of reducing the incidence of vascular complications and neuropathy. This study employed a quasi-experimental design, specifically a one-group pretest-posttest design with a control group. A probability sampling method—specifically simple random sampling—was used to select 60 respondents. Data collection involved the use of the DSMQ questionnaire and an observation sheet. The Wilcoxon test results yielded a p-value of 0.009 (p < 0.05), indicating a significant influence of diabetes mellitus self-management on the risk of complications at the Harapan Jaya Clinic in Saentis Village. Self-management practices should be implemented among diabetes mellitus patients to prevent the risk of complications. Nurses need to provide education on diabetes mellitus self-management to patients, enabling them to independently manage the disease and avoid the risk of complications.